Moderate Emissions Grandfathering1. (October 2014) - Knight, Carl
Emissions grandfathering holds that a history of emissions strengthens an agent's claim for future emission entitlements. Though grandfathering appears to have been influential in actual emission control frameworks, it is rarely taken seriously by philosophers. This article presents an argument for thinking this an oversight. The core of the argument is that members of countries with higher historical emissions are typically burdened with higher costs when tran-sitioning to a given lower level of emissions. According to several appealing views in political philosophy (utilitarianism, egalitarianism, prioritarianism and sufficientarianism) they are therefore entitled to greater resources, including emission entitlements, than those in similar positions but with lower emissions. This grandfathering may play an especially important role in allocating emission entitlements among rich countries.